2020
DOI: 10.1111/sode.12488
|View full text |Cite
|
Sign up to set email alerts
|

“Where’s your bum brain?” Humor, social understanding, and sibling relationship quality in early childhood

Abstract: Shared humor is a central feature of children's close relationships and a universal, integral part of human experience that is characterized by playful incongruity or, a benign conflict between what is expected and experienced

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 58 publications
3
19
0
Order By: Relevance
“…We also found that children who engaged in playful teasing with their sibling during dress-up play were more likely to have made reference to cognitive states while playing alone with the Playmobil set (e.g., “Kate [Playmobil figure] does not know where it is.”). This finding corroborates and extends previous work showing that children’s humor production is associated with their propensity to refer to cognitive states within sibling interactions (Paine et al, 2021). Although our findings suggest that humor production is associated with thinking about others’ minds, the cross-sectional nature of these associations preclude us from making any conclusions about causality.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We also found that children who engaged in playful teasing with their sibling during dress-up play were more likely to have made reference to cognitive states while playing alone with the Playmobil set (e.g., “Kate [Playmobil figure] does not know where it is.”). This finding corroborates and extends previous work showing that children’s humor production is associated with their propensity to refer to cognitive states within sibling interactions (Paine et al, 2021). Although our findings suggest that humor production is associated with thinking about others’ minds, the cross-sectional nature of these associations preclude us from making any conclusions about causality.…”
Section: Discussionsupporting
confidence: 91%
“…We also investigated theoretically predicted associations between children’s humor production and their tendency to engage in pretense and their social understanding skills. As in previous studies (Paine, Howe, et al, 2019; Paine et al, 2021), most children produced humor with their sibling during play. Children most often performed incongruities, shared preposterous statements or humorous anecdotes, and engaged in playful teasing.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations